Characteristic of Elite Male 800-m Runner’s Race Performance Based on Hybrid Computing Methods - Chao Chen; Jie Ma; Jinzhuang Song; Shengbao He; Mengchao Tan (Applied Bionics and Biomechanics)
The purpose of the study was to analyze the characteristics of elite men’s 800-m race performance, which help coaches to obtained the winning experience of 800-m race and prepare for athletes’ training more efficiently. Hybrid computing methods were applied to analyze athletes’ race performance. The study found that the competitive capability of elite athletes mainly include maximal speed running, speed endurance, and even pacing running. The maximal speed advance from 700–800 to 100–200-m sector, the velocity is also increase at the same time. The first peak speed (100–200 m) is higher than the second (500–600 m). Reduce the 0–400 m split times could be contributing to achieve personal best. 200–400 m is the even pacing phase which have the function of adjust physiological condition and preserve energy. The speed endurance was the most important factor to won the 800-m race. Place in permanent ranking and adopt the follow-running tactic can increase the odds to be medalist.